2015
DOI: 10.1186/s40560-015-0112-5
|View full text |Cite
|
Sign up to set email alerts
|

A review of sepsis-induced cardiomyopathy

Abstract: Sepsis-induced cardiomyopathy is a reversible myocardial dysfunction that typically resolves in 7–10 days. It is characterized by left ventricular dilatation and depressed ejection fraction. However, many uncertainties exist regarding the mechanisms, characteristics, and treatments of this condition. Therefore, this review attempts to summarize our current knowledge of sepsis-induced cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
219
2
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(256 citation statements)
references
References 65 publications
1
219
2
14
Order By: Relevance
“…Recently, it has been suggested that phosphodiesterase III inhibitors may also be useful for septic cardiomyopathy 1, 2. Our patients did not respond well to conventional therapy.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Recently, it has been suggested that phosphodiesterase III inhibitors may also be useful for septic cardiomyopathy 1, 2. Our patients did not respond well to conventional therapy.…”
Section: Discussioncontrasting
confidence: 60%
“…As a result, ECG shows LV dysfunction and dilatation without regional dysfunction. These findings are useful to describe the difference from ischemic cardiac failure 1, 2. In sepsis, both the peripheral oxygen requirement and cardiac output are generally increased.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Exotoxins like streptolysin O [23] or pneumolysin with cardiotoxic potential cause septic cardiomyopathy leading to arrhythmias [24]. In pneumoccal infections, platelet-activating factor receptor activation by the bacterial cell wall plays the same role [25].…”
Section: Arrhythmias In Septic States -Causative Factorsmentioning
confidence: 99%
“…The myocardium is functionally and structurally injured by inflammatory cytokines and mitochondrial dysfunction [10]. It has a classical triad: affecting both ventricles and causing global ventricular dysfunction (decreasing biventricular ejection fraction), left ventricular dilatation (diastolic dysfunction with elevated left ventricular end-diastolic volume), and recovery in 7-10 days.…”
Section: Specific Reversible Cardiomyopathiesmentioning
confidence: 99%